Viennese Style in Viennese Waltzes: An Empirical Study of Timing in the Recordings of The Blue Danube - Jian Yang (Musicologica Austriaca, 2022)
It is widely assumed that Viennese orchestras, especially the Vienna Philharmonic Orchestra (VPO), possess distinctive qualities in their performance of Viennese waltzes. This article sets out to provide empirical evidence of this hypothesis. Focusing on the parameter of timing, it analyzes the rhythm and tempo in 34 recordings of Johann Strauss II’s The Blue Danube, widely regarded as the best-known Viennese waltz. The results yield the following findings: (1) At the beat level, Viennese orchestras, particularly the VPO, widely employ an uneven 3-beat pattern of “short-long-medium,” whereas non-Viennese orchestras play the three beats with relatively even lengths; (2) at the phrase level, the VPO tends to demonstrate much more rubato, which goes hand in hand with “spiral tempo-dynamic shaping”; (3) at the sectional level, larger-scale and more structural tempo modifications, especially the “long-range accelerando,” are found in the VPO’s recordings. Some of these features seem to be associated less with the conductors than with the orchestra’s own performance practice. In addition, the choreographic factors and the gala circumstances of the Vienna New Year’s Concert may also play a role in the stylistic distinctiveness of Viennese orchestras.